General Biology - Doerder, Paul; Gibson, Ralph; Open Textbook Library (Open Textbook Library, 2015)
The word biology means, "the science of life", from the Greek bios, life, and logos, wordor knowledge. Therefore, Biology is the science of Living Things. That is why Biology issometimes known as Life Science.
1 Getting Started -- 2 Biology - The Life Science -- 3 The Nature of Molecules -- 4 Chemical Building Blocks of Life -- 5 Life: History and Origin -- 6 Cells -- 7 Cell structure -- 8 Structure of Eukaryotic cells -- 9 Membranes -- 10 Cell-cell interactions -- 11 Energy and Metabolism -- 12 Respiration: harvesting of energy -- 13 Photosynthesis -- 14 Sexual reproduction -- 15 Genetics -- 16 Gregor Mendel and biological inheritance -- 17 DNA: The Genetic Material -- 18 Gene expression -- 19 Gene regulation -- 20 Mutation -- 21 Recombinant DNA technology -- 22 Classification of Living Things -- 23 Multicellular Photosynthetic Autotrophs -- 24 Chordates -- 25 Tissues and Systems -- 26 Epithelial tissue -- 27 Connective tissue -- 28 Muscle tissue -- 29 Vertebrate digestive system -- 30 Circulatory system -- 31 Respiratory system -- 32 Sensory systems -- 33 Additional material -- 34 Glossary -- 35 Contributors -- 36 Licenses
In English.
Description based on online resource
Keywords: Science -- Textbooks; Biology -- Textbooks